Institutional Development of Village-Owned Enterprises in Managing Water Resources and Tourism Villages Through a Stakeholder Collaboration Approach - Amirul Mustofa; Eny Haryati; Litafira Syahadiyanti; Sri Kamariyah (Pt. Anagata Sembagi Education, 2024)
This study aims to analyze the development of Village-Owned Enterprises (VOE) in managing water resources and tourism villages through a stakeholder collaboration approach. VOE strategically optimizes local potential, including sustainable water resource management and tourism village development to boost the local economy. This research uses a qualitative method with a case study approach in villages with abundant tourism potential and water resources. We collected data through in-depth interviews with key stakeholders, such as village government officials, VOEs managers, and local community members involved in tourism village development. The results show that collaboration among stakeholders, involving the village government, VOEs, and the community, creates an effective synergy in managing water resources and developing tourism villages. VOEs serve as the main drivers coordinating various interests and resources, while active community participation is critical to maintaining the sustainability of the programs. Additionally, policy support from the village government and partnership patterns help overcome the technical and financial challenges VOEs face. This study concludes that a collaborative approach among stakeholders is an effective strategy for developing VOEs to manage water resources and tourism villages. Successful implementation requires a shared commitment, transparency, and good communication among all parties.